Solar light driven hybrid pyrite- eggshell for reactive red 120 dye degradation - Nur Ellya Natasha, Zakaria; Hamidah, Abdullah (2021)
Dyes are one of the most hazardous chemical compound classes found in industrial effluents and need to be treated. Reactive dyes represent an important portion of the commercial synthetic dyes, which have negative effects on human and also to aquatic life which can be treated by using photocatalytic reaction and by using adsorption. Wastewater that contain synthetic dye can be treated by using photocatalytic reaction and adsorption. Pyrite was used as photocatalyst and eggshell as adsorbent due to their low cost and environmental friendly.